Targeted Alpha Radiopharmaceutical Therapy and Key Considerations for Nuclear Medicine Technologists - Bolin, Julie; Groves, Daryn (World Journal of Nuclear Medicine, 2025)
The use of radionuclides for targeted radiopharmaceutical therapy (RPT) is a rapidly evolving field in nuclear medicine and oncology. With the integration of imaging and therapy, therapeutic nuclear medicine has made remarkable progress in recent years. One particularly promising area of research is the use of α-emitting radionuclides, which possess unique physical properties that provide notable advantages, including the ability to target single tumor cells with high precision. Although the only targeted α therapy (TAT) currently approved by the United States Food and Drug Administration is 223Ra-dichloride for the treatment of castration-resistant prostate cancer with skeletal metastases, a search on clinicaltrials.gov yields a significant number of early- and late-stage clinical trials utilizing 223-Ra, 225-Ac, 211-At, 212-Pb, and 227-Th are in progress, indicating that more TATs are on the horizon. As the prevalence of use for TAT increases, it is important to consider the logistics of TAT administration and the requirements for radiation safety and patient discharge. This review aims to provide a comprehensive overview of the advancements, relevant clinical trials, and logistical considerations associated with targeted α RPT in oncology.
Keywords: alpha-particle; beta-particle; molecular target; radiopharmaceutical therapy; targeted α therapy